Incidence, Risk Factors and Consequences of Epilepsy-Related Injuries and Accidents: A Retrospective, Single Center Study - Willems, Laurent M.; Watermann, Nina; Richter, Saskia; Kay, Lara; Hermsen, Anke M.; Knake, Susanne; Rosenow, Felix; Strzelczyk, Adam (Frontiers in Neurology, 2018)
Introduction: This study was designed to evaluate risk factors and incidence of epilepsy-related injuries and accidents (ERIA) at an outpatient clinic of a German epilepsy center providing healthcare to a mixed urban and rural population of over one million inhabitants. Methods: Data acquisition was performed between 10/2013 and 09/2014 using a validated patient questionnaire on socioeconomic status, course of epilepsy, quality of life, depression, injuries and accidents associated with seizures or inadequate periictal patterns of behaviour concerning a period of three months. Univariate analysis, multiple testing and regression analysis were performed to identify possible variables associated with ERIA. Results: A total of 292 patients (mean age 40.8 years, range 18-86; 55% female) were enrolled and analyzed. Focal epilepsy was diagnosed in 75% of the patients. The majority was on an antiepileptic drug (AEDs) polytherapy (mean number of AEDs: 1.65). Overall, 41 patients (14.0%) suffered from epilepsy-related injuries and accidents in a three-month period. Besides lacerations (n=18, 6.2%), abrasions and bruises (n=9, 3.1%), fractures (n=6, 2.15%) and burns (n=3, 1.0%), 17 mild injuries (5.8%) were reported. In 20 (6.8% of the total cohort) cases, urgent medical treatment with hospitalization was necessary. Epilepsy-related injuries and accidents were related to active epilepsy, occurrence of generalized tonic-clonic seizures (GTCS) and drug-refractory course as well as reported ictal falls, ictal loss of consciousness and abnormal peri-ictal behaviour in the medical history. In addition, patients with ERIA had significantly higher depression rates and lower quality of life. Conclusion: ERIA and their consequences should be given more attention and standardized assessment for ERIA should be performed in every outpatient visit.